PENGARUH MODEL COLLABORATIVE WRITING DENGAN TEKNIK KERTAS BERGILIR TERHADAP KEMAMPUAN MENULIS TEKS CERITA INSPIRATIF KELAS VIII SMP NEGERI 36 MEDAN - Aristianti Gultom, Endang; Hutagalung, Trisnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Collaborative Writing model with the rotating paper technique on the ability of eighth-grade students at SMP Negeri 36 Medan to write inspirational narrative texts. The study was based on the theories of Collaborative Writing, Direct Instruction, the rotating paper technique, and writing skills. An experimental method with a Posttest-Only Control Group Design was employed. The sample consisted of 50 students divided into an experimental class and a control class. The results showed that the experimental class obtained a mean score of 86.92, while the control class achieved a mean score of 74.12. The hypothesis test using the Independent Samples t-Test revealed that tcount = 5.942 > ttable = 2.010 and Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between the two classes. The effect size analysis produced a Cohen’s d value of 1.6805, categorized as very large. Therefore, the Collaborative Writing model with the rotating paper technique significantly improved students’ ability to write inspirational narrative texts. Keywords: Collaborative Writing, rotating paper technique, inspirational narrative text, writing ability.